2001
DOI: 10.1002/1096-9071(200103)63:3<203::aid-jmv1001>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Targets of a protease inhibitor, KNI-272, in HIV-1-infected cells

Abstract: The targets of a protease inhibitor, KNI-272, in the HIV-1 life cycle were investigated in this study. Neither expression of HIV-1 Gag proteins nor production of virus particles was detected in cells infected acutely with HIV-1 cultured in the presence of KNI-272. Although HIV-1 proviral DNA was detected in the cells by PCR, the inhibitor depressed the amount of the proviral DNA in a concentration dependent manner. These results indicate that one of the targets of KNI-272 occurs in the stage before the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…On the basis of the NC cleavage observed in the EIAV capsid, we hypothesized that the PR is active in the early phase of the virus life cycle and that the NC protein is one of the targets of PR processing ( 18 , 42 , 43 ). Several research groups, including ours, found an inhibitory effect of PR inhibitors in the early phase of viral replication ( ), supporting this assumption, while others did not observe such an effect ( ). When the required zinc removal and the acidic pH optimum of the PR are taken into account, the likely place of the early-phase NC processing is the endosome for viral particles entering the cells through receptor-mediated endocytosis.…”
Section: Discussionsupporting
confidence: 67%
“…On the basis of the NC cleavage observed in the EIAV capsid, we hypothesized that the PR is active in the early phase of the virus life cycle and that the NC protein is one of the targets of PR processing ( 18 , 42 , 43 ). Several research groups, including ours, found an inhibitory effect of PR inhibitors in the early phase of viral replication ( ), supporting this assumption, while others did not observe such an effect ( ). When the required zinc removal and the acidic pH optimum of the PR are taken into account, the likely place of the early-phase NC processing is the endosome for viral particles entering the cells through receptor-mediated endocytosis.…”
Section: Discussionsupporting
confidence: 67%
“…Tetherin is a protein highly expressed in plasmacytoid dendritic cells (pDCs), the major producers of type I IFN, and in some cancer cells, while lower basal levels of expression are detected in bone marrow stromal cells, terminally differentiated B cells, macrophages, and T cells [100-104]. Its expression is strongly induced by type I IFNs in virtually all cell types [99,101,105-107], indicating that it is likely part of the innate defense response to virus infections.…”
Section: Role Of Vpu In Hiv-1 Release and Transmissionmentioning
confidence: 99%